Internalisasi Nilai-Nilai Pendidikan Akhlak pada Anak Usia Dini melalui Media Buku Balita Berakhlak Mulia - Ulpaini Roudhotur Rohima; Muru'atul Afifah; Yusfar Ramadhan (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2022)
This study discusses the importance of instilling moral education in early childhood, where at this time children experience a golden age in their development, children easily learn from the environment. So that at this time is the most appropriate time to internalize the values of moral education into children's identities with a variety of media, one of which is story books. The purpose of this study is to determine the process of internalizing the values of moral education contained in the book